A bone repair composite, its preparation method and application

CN117582555BActive Publication Date: 2026-10-27ZHONG DING KAI RUI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311695294.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-12
Publication Date
2026-10-27
Estimated Expiration
2043-12-12

AI Technical Summary

Technical Problem

但是这些材料与真正的骨组织的组成、性能和功能存在较大差异

Benefits of technology

[0016]本发明提供的以芦荟粘液为固化液的含有植酸盐的骨修复复合体含具有抗菌、消炎的植酸组分和容易被吸收的甘油硫酸盐以及能够调节钙含量和加速固化的硫酸盐,同时含有成骨元素有机钙、磷,具有可自凝固、pH中性、全降解的特性,还具有抗菌、抑炎等功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004600310580000031
    Figure BDA0004600310580000031
Patent Text Reader

Abstract

The present application relates to a kind of bone repair complex and its preparation method and application;Belong to bone repair material field.The present application is with glycerol phosphate, soluble phytate and sulfate as solid phase, with aloe mucilage as solidification liquid, and a kind of bone repair complex is prepared.The bone repair complex can provide osteogenesis component in osteogenesis cycle, promote bone trauma and defect repair and function recovery, meet the requirements of bone tissue repair and function recovery, and can be absorbed by tissue entirely.In addition, the bone repair complex obtained by the present application also has antibacterial, anti-inflammatory and other functions, which can reduce redness, exudation and other surgical infections caused by bacterial infection and inflammation during use, and can be widely used in bone trauma, defect repair and reconstruction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bone repair materials, specifically relating to a bone repair composite, its preparation method, and its application. Background Technology

[0002] Terrestrial animals, including mammals and birds, have skeletons that form the support system of their entire bodies, determining their ability to walk, move, and fly—essentially essential for daily survival. Studies on the changes in calcium and phosphorus levels during egg incubation show that during embryonic development, the albumen provides 20.2% of the calcium, the yolk provides 10.0%, and the shell provides 69.8%, making the shell the primary calcium source for embryonic development. Except for the sixth embryonic stage, the phosphorus content in the yolk continuously decreases, indicating that the yolk plays a dominant role in phosphorus supply during embryonic development. The changes in calcium and phosphorus content in the albumen and yolk exhibit a degree of complementarity. The calcium and phosphorus content in the embryo increases daily, but the rate of increase in calcium is far greater than that of phosphorus. This suggests that skeletal development is regulated by DNA, with tissues autonomously adjusting calcium and phosphorus content to gradually change the calcium-to-phosphorus ratio and form skeletal tissue. Therefore, the initial components of bone are not the commonly known complex of bone apatite and collagen found in mature bone tissue, but rather are gradually formed within the embryo by calcium from proteins, yolks, and shells, as well as phosphorus from the yolk, under the regulation of DNA. According to this process, the repair of damaged bone tissue also needs to start from its origin, providing it with osteogenic components that can be absorbed and assimilated by the tissue, and gradually absorbed and assimilated into bone tissue under the regulation of DNA.

[0003] Currently, the most popular bone repair and reconstruction materials in China are hydroxyapatite and calcium silicate. The former is the main inorganic component of mature bone tissue, and the latter is a major type of cement used in construction. Both have good biocompatibility and safety, and can exist in bone tissue for a long time to occupy vacancies and supplement missing tissue. However, these materials differ greatly from real bone tissue in composition, performance and function. The main differences are: (1) They cannot be completely absorbed and assimilated by bone tissue and will remain in the tissue for a long time, especially for bone tissue that needs to be completely repaired and reconstructed, it is difficult to achieve the reconstruction goal; (2) Their density, hardness and mechanical properties are very different from bone tissue. When the tissue encounters heating, cooling and stress, their conductivity is difficult to match completely, and stress concentration will form at the interface, making the human body feel uncomfortable; (3) They are very stable in the tissue, blood cannot pass through them, they cannot carry them to circulate freely, blood vessels and fibers cannot form and pass through them, and they cannot be assimilated into the tissue. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention utilizes glycerophosphate, soluble phytate, and sulfate as the solid phase and aloe vera mucilage as the curing liquid to prepare a bone repair complex. This bone repair complex can provide osteogenic components during the osteogenic cycle, promoting the repair and functional recovery of bone trauma and defects, meeting the requirements for bone tissue repair and functional recovery, and is fully absorbable by tissues. Furthermore, the bone repair complex obtained by this invention also possesses antibacterial and anti-inflammatory functions, reducing surgical infections caused by bacterial infection and inflammation during use, such as redness, swelling, and exudation. It can be widely applied in the repair and reconstruction of bone trauma and defects.

[0005] The technical solution of the present invention:

[0006] The first technical problem to be solved by the present invention is to provide a bone repair composite, wherein the raw materials of the bone repair composite include a solid phase and a curing liquid, wherein the solid phase includes glycerophosphate, soluble phytate and sulfate; and the curing liquid is aloe vera mucus.

[0007] Furthermore, the ratio of the curing liquid to the solid phase is 0.5–1.5 mL: 1.0 g.

[0008] Furthermore, the solid phase comprises 30-60 parts by weight of glycerol phosphate, 100-200 parts by weight of soluble phytate, and 40-100 parts by weight of sulfate.

[0009] Furthermore, the soluble phytate is prepared from phytic acid and metal hydroxides or carbonates, wherein the molar ratio of phytic acid to metal hydroxides or carbonates is 1:2 to 5, the pH of the soluble phytate is 6.50 to 7.2, and the metal hydroxides or carbonates are selected from the hydroxides or carbonates of calcium, magnesium, strontium, zinc, and yttrium.

[0010] Furthermore, the glycerophosphate is selected from calcium glycerophosphate, magnesium glycerophosphate, or zinc glycerophosphate.

[0011] Furthermore, the sulfate is anhydrous or hemihydrate sulfate, and the sulfate is selected from calcium sulfate, magnesium sulfate, zinc sulfate, strontium sulfate, or yttrium sulfate.

[0012] Furthermore, the aloe vera mucilage is prepared by the following method: the aloe vera is peeled, cut into pieces, crushed, filtered, and sterilized to obtain the aloe vera mucilage. The aloe vera is preferably Aloe barbadensis, Aloe chinensis, Aloe arborescens, Aloe saponaria, Aloe vera var. shangnong, or Aloe scape.

[0013] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned bone repair complex. The preparation method is to first mix glycerophosphate, soluble phytate and sulfate to form a solid phase, then mix aloe vera mucus and the solid phase in a ratio of 0.5-1.5 mL:1.0 g to form a mixture; finally, the mixture is solidified to obtain the bone repair complex.

[0014] The third technical problem to be solved by the present invention is to point out the use of the above-mentioned bone repair complex in bone defects, bone injuries, bone trauma or bone reconstruction.

[0015] The beneficial effects of this invention are:

[0016] The bone repair complex containing phytate and using aloe vera mucus as a curing liquid provided by this invention contains phytate components with antibacterial and anti-inflammatory properties, easily absorbed glyceryl sulfate, and sulfate that can regulate calcium content and accelerate curing. It also contains osteogenic elements organic calcium and phosphorus, and has the characteristics of self-coagulation, pH neutrality, and complete degradation. It also has antibacterial and anti-inflammatory functions.

[0017] The bone repair composite obtained by this invention has the characteristics of being able to gradually degrade from the side in contact with bone tissue, providing components throughout the entire process of bone tissue repair and reconstruction from the wound surface, and promoting tissue repair and reconstruction.

[0018] The bone repair composite obtained in this invention exhibits enhanced strength after curing, including early defect support, gradual degradation and tissue fusion, and absorption and replacement by tissue. It also provides various organic and inorganic components that promote bone tissue regeneration, improving tissue regeneration and reconstruction. Its degradation rate can be controlled according to its composition, matching bone tissue regeneration and reconstruction. Furthermore, it reduces surgical infections caused by bacterial infection and inflammation, such as redness and swelling, during use, and can be widely applied in the repair and reconstruction of bone trauma and defects. Specific implementation plan:

[0019] This invention utilizes glycerophosphate, soluble phytate, and sulfate as the solid phase and aloe vera mucilage as the curing liquid to prepare a bone repair complex. This bone repair complex can provide osteogenic components during the osteogenic cycle, promoting the repair and functional recovery of bone trauma and defects, meeting the requirements for bone tissue repair and functional recovery, and is completely absorbed by tissues. Furthermore, the bone repair complex obtained by this invention also possesses antibacterial and anti-inflammatory functions, reducing surgical infections caused by bacterial infection and inflammation during use, such as redness, swelling, and exudation. It can be widely used in the repair and reconstruction of bone trauma and defects.

[0020] The aloe vera mucilage of this invention is prepared as follows: Fresh, plump, and tender aloe vera leaves and stems are selected, preferably those with relatively thick flesh and roughly the same size. The aloe vera stems and leaves are peeled off from the bottom, removing the green skin and leaving jelly-like gelatinous pieces. The size of the pieces is determined by the capacity of the blender used, generally 1-2 cm in length, width, and height. The jelly-like gelatinous pieces are then placed in a blender and blended finely for 3-10 minutes. A general household blender or a pharmaceutical blender can be used. The mixture is then filtered using a No. 2 or No. 3 glass funnel or a filter screen or filter cloth with a pore size of 5-50 μm. The filtrate is subjected to ultra-high temperature instantaneous sterilization (heated to 135℃-140℃ in a continuous flow state through a heat exchanger, held for 3-4 seconds). Afterward, it is placed in a sterilized container, sealed, and stored in a refrigerator at -18℃. The resulting aloe vera mucilage is used as a solidification liquid for later use. The aloe vera mucilage of this invention has a triple function of solidification, providing nutrition, and increasing strength.

[0021] The soluble phytate (I) of this invention can be prepared by the following method: When preparing the soluble phytate, a 50% aqueous solution of phytic acid is used as the raw material, and hydroxides or carbonates of metals such as calcium hydroxide, magnesium hydroxide, zinc carbonate, strontium hydroxide, and yttrium carbonate are used as divalent metal ion donors. When a metal hydroxide is used as a divalent metal ion donor, the reactions involved are as follows:

[0022] Where M represents calcium, magnesium, strontium, zinc, yttrium, etc., the composition and solubility of phytates vary depending on the value of m. For example, if m = 3, (m... Ca =2,m Mg =1), the resulting phytate structure is:

[0023] By controlling the value of m and the type of metal ion, various soluble phytates can be obtained. m can be an integer of 2, 3, 4, or 5, or a decimal such as 2.2, 2.5, or 3.3. If m = 6, a stoichiometric composition and qualitative precipitation will occur, and the resulting phytate will be difficult to dissolve or only slightly soluble in water or body fluids. The pH of this soluble phytate is controlled between 6.50 and 7.20 to maintain its near-neutral state, allowing it to remain continuously soluble or only slightly soluble in pure water or simulated body fluids. The soluble divalent phytic acid salt, as component (I) of this invention, has the following general structural formula:

[0024] The specific steps are as follows: A certain amount of 50wt% phytic acid solution is transferred into a stirred reaction vessel under nitrogen protection. While stirring, a saturated calcium hydroxide solution, or ultrafine calcium hydroxide nanopowder, or other metal hydroxides or carbonates such as strontium hydroxide, magnesium hydroxide, and calcium carbonate are added. The amount is controlled within the range of m less than 5. When the pH reaches 6.5-7.2, the addition of materials is stopped. The mixture is stirred at room temperature for 10-30 minutes under nitrogen protection, then concentrated by vacuum distillation, filtered using a No. 4 glass funnel, washed twice with anhydrous ethanol, and then dried under vacuum at 50-60℃ for 6-12 hours to obtain soluble phytate as component (I) for later use. This invention controls the ratio of phytic acid to divalent metal ions (not greater than 5) to obtain unsaturated divalent phytic acid ion salts that can dissolve slowly (a ratio of 6 is saturated and difficult to dissolve) as donors of osteogenic elements phosphorus and metal ions.

[0025] The solid phase of this invention is prepared by the following method: soluble phytate (I) and glycerol phosphate. (calcium glycerol phosphate) Magnesium glycerol phosphate Component (II), sulfate (calcium sulfate hemihydrate) The proportions of component (III) (such as anhydrous calcium sulfate) are: 30-60 parts by weight of glycerophosphate, 100-200 parts by weight of soluble phytate and 40-100 parts by weight of sulfate.

[0026] The selection of the proportions aims to ensure sufficient osteogenic elements, complete absorption and degradation, and a near-neutral pH, while also providing suitable curing time and post-curing strength. This invention utilizes highly soluble glycerophosphates to adjust the solubility and pH of the composite, resulting in a suitable degradation rate and acid-base environment conducive to osteogenic formation and bone tissue remodeling; and uses sulfates (such as calcium sulfate hemihydrate) to adjust the calcium-phosphorus ratio and achieve self-coagulation properties. All three types of solid-phase raw materials used in the preparation and selection of this invention are completely degraded and absorbed by tissues.

[0027] The specific steps are as follows: Mix components (I), (II), and (III) in a certain mass ratio, and perform colloid milling using a ball mill or tetrahydrofuran as the medium. The temperature during the ball milling and colloid milling processes should not exceed 50℃; the ball milling speed is 100-200 r / m, and the colloid milling speed is 150-300 r / m. After completing the ball milling or colloid milling process, the mixture of components (I), (II), and (III) is dried under vacuum at a temperature of 50-80℃ to obtain a solid phase. In order to ensure thorough mixing, especially sufficient diffusion in the aloe vera mucus and chemical and hydration reactions at the interface, the smaller the particle size of the solid phase, the better. Considering the efficiency of ball milling or colloid milling, a particle diameter of less than 10 micrometers is sufficient to meet the requirements of subsequent experiments.

[0028] The bone repair composite of this invention is prepared by the following method: A solid phase and prepared aloe vera mucus are mixed and blended uniformly in a certain ratio to form a bone repair mixture containing phytate, with aloe vera mucus as the curing liquid. The selected aloe vera mucus, after being combined with the solid phase, can enhance the strength after curing and provide more nutrients to the tissue. The general ratio is 0.5–1.5:1.0 (mL / g) of aloe vera mucus (L): solid phase (S). Finally, the resulting mixture is cured to obtain the bone repair composite. The curing of the mixture can be accomplished through the following steps: the resulting mixture is loaded into a mold to form a test sample, or shaped into the desired shape; or, the mixture is thoroughly stirred to form a paste, which is then injected into the wound or defect site using a syringe or after being shaped into the desired form. The curing time is 10–60 minutes, with 15–45 minutes being the optimal surgical time. Alternatively, it can be pre-formed into granules for use as a filler during surgery.

[0029] The following detailed description of specific embodiments further illustrates the above-described content of the present invention. However, this should not be construed as limiting the scope of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention, and the specific scope of protection is detailed in the claims.

[0030] Example 1 (In phytate, m=3, which is calcium alone)

[0031] 1. Preparation of Aloe Vera Mucus: Select 1 kg of fresh, plump, and tender Aloe vera leaves and stems. Peel the aloe vera stems and leaves from the bottom, remove the green skin, leaving jelly-like gel pieces approximately 1 cm in length, width, and height. Then, put the jelly-like gel pieces into a high-speed blender and blend until finely ground for 3 minutes. After blending, filter using a No. 2 glass funnel. The filtrate is then sterilized using ultra-high temperature instantaneous sterilization (heated to 135℃~140℃ in a continuous flow state through a heat exchanger and held for 4 seconds). It is then poured into a sterilized container, sealed, and stored in a refrigerator at -18℃. 500 mL of the obtained aloe vera mucus is reserved as a solidification solution.

[0032] 2. Preparation of Component (I) Soluble Phytate: 1.2 L of 50% phytic acid solution was added to a 5 L reactor flask equipped with nitrogen protection and stirring. While stirring, nano-calcium carbonate was gradually added, and stirring was continued until the pH reached 6.7. The addition of material was then stopped, and the total amount added was 300 g. The mixture was stirred at room temperature under nitrogen protection for 30 minutes, then concentrated to 500 mL by vacuum distillation. The solution was filtered through a No. 4 glass funnel, washed twice with anhydrous ethanol, and then dried under vacuum at 50 °C for 8 hours to obtain 720 g of soluble tricalcium phytate.

[0033] 3. A composite of soluble tricalcium phytate (I), calcium glycerophosphate (II), and calcium sulfate hemihydrate (III). 150 g of soluble tricalcium phytate (I), 45 g of calcium glycerophosphate (II), and 65 g of calcium sulfate hemihydrate (III) were weighed. After mixing, the mixture was ball-milled at 35°C at a low speed of 150 r / m. After ball milling, the composite of components (I), (II), and (III) was dried under vacuum at 60°C for 6 hours to obtain a solid phase.

[0034] 4. Solidification of Aloe Vera Mucus with Solid Phase. Weigh 50g of the solid phase obtained in step 3 and add 30mL of the aloe vera mucus prepared in step 1, mix well. Place the mixed product into a mold to form a test sample, or shape it as desired, thus obtaining the bone repair composite.

[0035] 5. Performance research and evaluation methods for bone repair complexes. The performance of the samples obtained in the embodiments and comparative examples of this invention was characterized and evaluated using the following methods:

[0036] (1) Sample preparation: Take 20g of bone repair composite, add 10mL of water for injection, stir for 2 minutes, press it into a porous polytetrafluoroethylene mold with a pore diameter of 6mm and a height of 12mm, eject it after 5 minutes, and let it dry naturally in an environment with a temperature of 25℃ and a humidity of 60%. Determine its curing time (the curing time of the sample is determined according to ISO 9597-2008 standard using a Vicat apparatus); the calculation begins after the curing liquid is added to the sample powder, and ends when the final setting needle (0.5mm) of the Vicat apparatus can no longer leave a mark on the sample surface. The time calculated in this way is the final setting time of the bone cement; each sample is measured at least 5 times.

[0037] (2) Compression test method: Loading speed 1 mm / min:

[0038] Test the compressive strength after one day (1D), three days (3D), and five days (5D): After the sample (diameter 6mm, height 12mm) has been cured in air for 3 days, the mechanical strength of the sample is measured using a universal mechanical testing instrument. Each sample is measured at least 5 times.

[0039] (3) Degradation test method: The injection-molded material was subjected to degradation test in PBS solution. The PBS preparation method is as follows: accurately weigh KH2PO4 (0.544g), Na2HPO4·12H2O (7.16g), NaCl (16g) and KCl (0.402g) and dissolve them in 2L of deionized water, and make up to volume with a volumetric flask. The pH measurement range is 7.2 to 7.4. Put the sample into a centrifuge tube and add a certain amount of PBS solution. The volume ratio of PBS solution to sample mass is 1g / 30mL. Then place the centrifuge tube containing the sample in a constant temperature shaking incubator at 37℃ and 80rpm / min. Take out the sample at 1 (1D), 1 week, 4 weeks, 12 weeks and 24 weeks, weigh it and calculate the weight loss rate. Three control groups were set up for each sample.

[0040] (4) pH measurement: pH meter was used to measure the supernatant of the sample. PBS was replaced every 7 days.

[0041] (5) Cytotoxicity and cell proliferation rate test: Prepare the extract according to the relevant provisions of GB / T16886 on biological materials, and calculate the proliferation rate of the standard extract compared with the blank.

[0042] (6) The obtained bone repair complex was implanted into the back of New Zealand white rabbits according to the requirements of GB / T16886 to observe its biocompatibility such as degradation and inflammation. Specifically, two 2.5g portions of bone repair complex were implanted into the muscles on both sides of the rabbit's spine, with three rabbits in each group. The effect was observed, and the operation was carried out in accordance with the requirements of GB / T16886.

[0043] Test results:

[0044] Setting time: 16 min.

[0045] Compressive strength: 1D: 25MPa; 3D: 50MPa; 5D: 65MPa.

[0046] Degradation results: 1D: 5.5%; 1w: 20.2%; 4w: 50.8%; 12w: 80.4%.

[0047] pH changes: 1D: 7.05, 1w: 6.95, 4w: 7.10; 12w: 7.33.

[0048] Cytotoxicity and cell proliferation rate: Grade 0; the standard extract showed a proliferation rate of 130% compared to the blank, and 155% after being diluted by half; compared to the blank culture medium, the resulting bone repair fusion extract provided more nutrients, promoted cell differentiation, and increased cell proliferation.

[0049] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0050] Example 2 (Phytate contains two divalent metal ions, calcium and magnesium. In phytate, m = 3, m Ca =2,m Mg =1)

[0051] 1. Preparation of aloe vera mucilage: Same as in Example 1.

[0052] 2. Preparation of Component (I) Soluble Phytate: 1.2 L of 50% phytic acid solution was added to a 5 L reactor flask under nitrogen protection and stirring. While stirring, 200 g of nano-calcium carbonate and 60 g of magnesium hydroxide were gradually added, and stirring was continued until the pH reached 6.8. The mixture was stirred at room temperature under nitrogen protection for 30 minutes, then concentrated to 500 mL by vacuum distillation. The solution was filtered through a No. 4 glass funnel, washed twice with anhydrous ethanol, and then dried under vacuum at 55 °C for 8 hours to obtain 700 g of soluble tricalcium phytate.

[0053] 3-5, Same as Example 1.

[0054] Test results:

[0055] Setting time: 12 min.

[0056] Compressive strength: 1D: 21MPa; 3D: 50MPa; 5D: 66MPa.

[0057] Degradation results: 1D: 9.5%; 1w: 22.8%; 4w: 51.5%; 12w: 85.7%.

[0058] pH changes: 1D: 7.10, 1w: 7.15, 4w: 7.30; 12w: 7.30.

[0059] Cytotoxicity and cell proliferation rate: Grade 0; the standard extract showed a proliferation rate of 135% compared to the blank, and 156% after being diluted by one time; compared to the blank culture medium, the resulting bone repair fusion extract provided more nutrients, cell differentiation, and proliferation.

[0060] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0061] Example 3 (The phytate contains two divalent metal ions, calcium and magnesium, m = 3.5, m Ca =3,m Mg =0.5 structure is:

[0062] )

[0063] 1. Preparation of aloe vera mucilage: Same as in Example 1.

[0064] 2. Preparation of Component (I) Soluble Divalent Phytic Acid Salt: 1.2 L of 50% phytic acid solution was added to a 5 L reaction vessel with nitrogen protection and stirring. While stirring, 300 g of nano-calcium carbonate and 30 g of magnesium hydroxide were gradually added, and stirring was continued until the pH reached 7.1. The mixture was stirred at room temperature for 30 minutes under nitrogen protection, then concentrated to 500 mL by vacuum distillation. The solution was filtered through a No. 4 glass funnel, washed twice with anhydrous ethanol, and then dried under vacuum at 55 °C for 8 hours to obtain 730 g of soluble tricalcium phytate.

[0065] 3-5, Same as Example 1.

[0066] Test results:

[0067] Setting time: 20 min.

[0068] Compressive strength: 1D: 25MPa; 3D: 55MPa; 5D: 70MPa.

[0069] Degradation results: 1D: 7.7%; 1w: 21.5%; 4w: 49.4%; 12w: 82.8%.

[0070] pH changes: 1D: 7.15, 1w: 7.31, 4w: 7.30; 12w: 7.28.

[0071] Cytotoxicity and cell proliferation rate: Grade 0; the standard extract showed a proliferation rate of 138% compared to the blank, and 159% after being diluted by one time; compared to the blank culture medium, the resulting bone repair fusion extract provided more nutrients, promoted cell differentiation, and increased cell proliferation.

[0072] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0073] Example 4 (The phytate contains two divalent metal ions, calcium and magnesium, m=4, m Ca =3,m Mg =1)

[0074] 1. Preparation of aloe vera mucilage: Same as in Example 1.

[0075] 2. Preparation of Component (I) Soluble Phytate: 1.2 L of 50% phytic acid solution was added to a 5 L reactor flask equipped with nitrogen protection and stirring. While stirring, 200 g of nano-calcium carbonate and 60 g of magnesium hydroxide were gradually added, and stirring was continued until the pH reached 7.1. The mixture was stirred at room temperature under nitrogen protection for 30 minutes, then concentrated to 500 mL by vacuum distillation. The solution was filtered through a No. 4 glass funnel, washed twice with anhydrous ethanol, and then dried under vacuum at 55 °C for 8 hours to obtain 700 g of soluble tricalcium phytate.

[0076] 3-5, Same as Example 1.

[0077] Test results:

[0078] Setting time: 18 min.

[0079] Compressive strength: 1D: 21MPa; 3D: 50MPa; 5D: 66MPa.

[0080] Degradation results: 1D: 9.5%; 1w: 22.8%; 4w: 51.5%; 12w: 85.7%.

[0081] pH changes: 1D: 7.10, 1w: 7.28, 4w: 7.30; 12w: 7.30.

[0082] Cytotoxicity and cell proliferation rate: Grade 0; the standard extract showed a proliferation rate of 144% compared to the blank, and 168% after dilution by one time; compared to the blank culture medium, the resulting bone repair fusion extract provided more nutrients, promoted cell differentiation, and increased cell proliferation.

[0083] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0084] Example 5 (Aloe vera was used, other aspects were the same as in Example 1)

[0085] 1. Preparation of Aloe Vera Mucus: Select 2 kg of fresh, plump, and tender Aloe vera stems. Peel the aloe vera stems and leaves from the bottom, remove the green skin, leaving jelly-like gel pieces approximately 1 cm in length, width, and height. Then, put the jelly-like gel pieces into a high-speed blender and blend until finely ground for 3 minutes. After blending, filter using a No. 2 glass funnel. Sterilize the filtrate using ultra-high temperature instantaneous sterilization (heated to 135℃~140℃ in a continuous flow state through a heat exchanger and held for 4 seconds). Pour into a sterilized container, seal, and store in a refrigerator at -18℃. 1200 mL of the obtained aloe vera mucus is reserved as a solidification solution.

[0086] 2-5, Same as Example 1.

[0087] Test results:

[0088] Setting time: 15 min.

[0089] Compressive strength: 1D: 20MPa; 3D: 44MPa; 5D: 61MPa.

[0090] Degradation results: 1D: 9.4%; 1w: 23.5%; 4w: 49.4%; 12w: 82.7%.

[0091] pH changes: 1D: 7.11, 1w: 7.16, 4w: 7.35; 12w: 7.30.

[0092] Cytotoxicity and cell proliferation rate: Grade 0; The proliferation rate of the standard extract was 135% compared with the blank, and 156% after dilution by half; Compared with the blank, i.e. the culture medium, the bone repair compound extract containing phytate with aloe vera mucus as the solidification liquid can provide more nutrients, promote cell differentiation and proliferation.

[0093] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0094] Example 6 (using magnesium glycerol phosphate)

[0095] 1-2, Same as Example 1.

[0096] 3. A composite of soluble tricalcium phytate (I), magnesium glycerol phosphate (II), and calcium sulfate hemihydrate (III). Weigh 150g of soluble tricalcium phytate (I), 45g of magnesium glycerol phosphate (II), and 65g of calcium sulfate hemihydrate (III). After mixing, ball milling was performed at 35℃ and a low speed of 150r / m. After ball milling, the composite of components (I), (II), and (III) was dried under vacuum at 60℃ for 6 hours to obtain a solid phase.

[0097] 4-5, Same as Example 1.

[0098] Test results:

[0099] Setting time: 20 min.

[0100] Compressive strength: 1D: 18MPa; 3D: 44MPa; 5D: 59MPa.

[0101] Degradation results: 1D: 11.4%; 1w: 25.8%; 4w: 55.3%; 12w: 88.3%.

[0102] pH changes: 1D: 6.90, 1w: 7.05, 4w: 7.23; 12w: 7.27.

[0103] Cytotoxicity and cell proliferation rate: Grade 0; The proliferation rate of the standard extract was 144% compared with the blank, and 164% after being diluted by half; Compared with the blank, i.e. the culture medium, the bone repair compound extract containing phytate with aloe vera mucus as the solidification liquid can provide more nutrients, and promote cell differentiation and proliferation.

[0104] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0105] Example 7 (The ratio of calcium sulfate hemihydrate differs from that in Example 1)

[0106] 1-2, Same as Example 1.

[0107] 3. Soluble tricalcium phytate (I) and calcium glycerophosphate (II) were combined with calcium sulfate hemihydrate (III). 150g of soluble tricalcium phytate (I), 45g of calcium glycerophosphate (II), and 90g of calcium sulfate hemihydrate (III) were weighed. After mixing, the mixture was ball-milled at 35℃ and at a low speed of 150 r / m. After ball milling, the three-component composite (I), (II), and (III) was dried under vacuum at 60℃ for 6 hours to obtain a solid phase.

[0108] 4-5, Same as Example 1.

[0109] Test results:

[0110] Setting time: 10 min.

[0111] Compressive strength: 1D: 23MPa; 3D: 52MPa; 5D: 70MPa.

[0112] Degradation results: 1D: 12.7%; 1w: 25.5%; 4w: 60.3%; 12w: 86.9%.

[0113] pH changes: 1D: 6.85.10, 1w: 7.01, 4w: 7.20; 12w: 7.31.

[0114] Cytotoxicity and cell proliferation rate: Grade 0; The proliferation rate of the standard extract was 135% compared with the blank, and 156% after dilution by half; Compared with the blank, i.e. the culture medium, the bone repair compound extract containing phytate with aloe vera mucus as the solidification liquid can provide more nutrients, promote cell differentiation and proliferation.

[0115] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0116] Example 8 (the proportions of components (I), (II), and (III) are different from those in other examples)

[0117] 1-2, Same as Example 1.

[0118] 3. A composite of soluble tricalcium phytate (I), calcium glycerophosphate (II), and calcium sulfate hemihydrate (III). Weigh 200g of soluble tricalcium phytate (I), 50g of calcium glycerophosphate (II), and 100g of calcium sulfate hemihydrate (III). After mixing, ball mill the mixture at 35℃ and a low speed of 150r / m. After ball milling, the composite of components (I), (II), and (III) is dried under vacuum at 60℃ for 6 hours to obtain a solid phase.

[0119] 4-5, Same as Example 1.

[0120] Test results:

[0121] Setting time: 17 min.

[0122] Compressive strength: 1D: 23MPa; 3D: 54MPa; 5D: 69MPa.

[0123] Degradation results: 1D: 10.4%; 1w: 23.3%; 4w: 54.3%; 12w: 84.3%.

[0124] pH changes: 1D: 6.95, 1w: 7.15, 4w: 7.35; 12w: 7.33.

[0125] Cytotoxicity and cell proliferation rate: Grade 0; The proliferation rate of the standard extract was 135% compared with the blank, and 156% after dilution by half; Compared with the blank, i.e. the culture medium, the bone repair compound extract containing phytate with aloe vera mucus as the solidification liquid can provide more nutrients, promote cell differentiation and proliferation.

[0126] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0127] Example 9 (different ratios of Aloe vera mucilage and three-component complex)

[0128] 1-3, Same as Example 1

[0129] 4. Solidification of Aloe Vera Mucus with Solid Phase. Weigh 50g of the solid phase obtained in step 3 and add 40mL of the aloe vera mucus prepared in step 1, mix well. Place the mixed product into a mold to form a test sample, or shape it as desired, thus obtaining the bone repair composite.

[0130] 5. Same as Example 1.

[0131] Test results:

[0132] Setting time: 28 min.

[0133] Compressive strength: 1D: 16MPa; 3D: 39MPa, 52MPa.

[0134] Degradation results: 1D: 12.1%; 1w: 23.9%; 4w: 54.5%; 12w: 88.4%.

[0135] pH changes: 1D: 6.80, 1w: 7.05, 4w: 7.20; 12w: 7.35.

[0136] Cytotoxicity and cell proliferation rate: Grade 0; The proliferation rate of the standard extract was 144% compared with the blank, and 164% after being diluted by half; Compared with the blank, i.e. the culture medium, the bone repair compound extract containing phytate with aloe vera mucus as the solidification liquid can provide more nutrients, and promote cell differentiation and proliferation.

[0137] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0138] Example 10 (Different ratios of Chinese aloe vera mucus and three-component complex)

[0139] Examples 1 to 3 are the same as in Example 5.

[0140] 4. Solidification of Aloe Vera Mucus and Solid Phase: Weigh 50g of the solid phase obtained in step 3 and add 35mL of Aloe Vera mucus prepared in step 1, mixing thoroughly. Pour the mixed product into a mold to form a test sample, or shape it as desired, thus obtaining the bone repair composite.

[0141] 5. Same as Example 1.

[0142] Test results:

[0143] Setting time: 25 min.

[0144] Compressive strength: 1D: 19MPa; 3D: 41MPa, 57MPa.

[0145] Degradation results: 1D: 11.7%; 1w: 23.5%; 4w: 54.1%; 12w: 88.2%.

[0146] pH changes: 1D: 6.85, 1w: 7.15, 4w: 7.23; 12w: 7.30.

[0147] Cytotoxicity and cell proliferation rate: Grade 0; The standard extract showed a proliferation rate of 149% compared to the blank, and 162% after being diluted by half; Compared to the blank (culture medium), the bone repair compound extract containing phytate and aloe vera mucus as the solidification liquid provided more nutrients, resulting in greater cell differentiation and proliferation.

[0148] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0149] Comparative Example 1: Calcium Phytate

[0150] Weigh 100g of calcium phytate (m=6), ball mill it until the particle size is about 10μm, then weigh another 50g, add 30mL of pure water, stir and mix to prepare the test sample.

[0151] Test results:

[0152] Setting time: 180 min.

[0153] Compressive strength: 1D: 5MPa; 3D: 5MPa, 6MPa.

[0154] Degradation results: 1D: 1.5%; 1w: disintegration.

[0155] pH change: 1D: 10.8, 1w: collapse.

[0156] Cytotoxicity and cell proliferation rate: Collapse prevented further experiments.

[0157] Comparative Example 2: Calcium Glycerate Phosphate

[0158] Weigh 100g of calcium glycerophosphate, ball mill it to a particle size of about 10μm, then weigh another 50g, add 30mL of pure water, stir and mix to prepare the test sample.

[0159] Test results:

[0160] Setting time: 210 min.

[0161] Compressive strength: 1D: 7MPa; 3D: 9MPa, 9MPa.

[0162] Degradation result: 1D: Collapse.

[0163] pH change: 1D: 11.2, disintegration.

[0164] Cytotoxicity and cell proliferation rate: Collapse prevented further experiments.

[0165] Comparative Example 3: Calcium Sulfate Hemihydrate

[0166] Weigh 100g of calcium sulfate hemihydrate, ball mill it to a particle size of about 10μm, weigh 50g, add 30mL of pure water, stir and mix to prepare the test sample.

[0167] Test results:

[0168] Setting time: 5 min.

[0169] Compressive strength: 1D: 9MPa; 3D: 15MPa; 5D: 32MPa.

[0170] Degradation results: 1D: 18.7%; 1w: 35.5%; 4w: 100%.

[0171] pH change: 1D: 5.85, 1w: 6.44, 4w: 7.10.

[0172] Cytotoxicity and cell proliferation rate: Grade 1; the standard extract showed an 80% proliferation rate compared to the blank, and an 85% proliferation rate after being diluted by one time; the acidity was stronger than that of the blank culture medium, which was not conducive to cell growth.

[0173] Post-operative wound: No redness, swelling, oozing, or fluid accumulation.

[0174] Comparative Example 4 is the same as Example 1, except that water is used as the curing solution.

[0175] Setting time: 30 min.

[0176] Compressive strength: 1D: 12MPa; 3D: 26MPa; 5D: 35MPa.

[0177] Degradation results: 1D: 11.4%; 1w: 22.7%; 4w: 53.6%; 12w: 84.4%.

[0178] pH changes: 1D: 7.10, 1w: 7.35, 4w: 7.28; 12w: 7.34.

[0179] Cytotoxicity and cell proliferation rate: Grade 0; the proliferation rate of the standard extract was 110% compared with the blank, and 127% after dilution by one time.

[0180] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0181] Compared to the bone repair composite prepared using aloe vera mucus as the curing liquid in Example 1, the material obtained in Comparative Example 4 had a longer curing time, faster degradation, slightly lower cell proliferation, and significantly reduced compressive strength.

[0182] Comparative Example 5 is the same as Example 1, except that calcium sulfate is removed.

[0183] Setting time: 60 min.

[0184] Compressive strength: 1D: 8MPa; 3D: 12MPa; 5D: 15MPa.

[0185] Degradation results: 1D: 13.4%; 1w: 26.3%; 4w: 51.7%; 12w: 85.1%.

[0186] pH changes: 1D: 7.40, 1w: 7.56, 4w: 7.61; 12w: 7.50.

[0187] Cytotoxicity and cell proliferation rate: Grade 0; the standard extract showed a proliferation rate of 120% compared to the blank, and a proliferation rate of 125% after dilution by one time.

[0188] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0189] Compared to Example 1 which contains calcium sulfate, the solidification time is significantly increased, degradation is accelerated, cell proliferation is slightly lower, pH is significantly increased, and compressive strength is significantly reduced.

[0190] Comparative Example 6 is the same as Example 1, except that calcium glycerophosphate is removed.

[0191] Setting time: 22 min.

[0192] Compressive strength: 1D: 15MPa; 3D: 28MPa; 5D: 49MPa.

[0193] Degradation results: 1D: 5.4%; 1w: 16.7%; 4w: 35.4%; 12w: 65.81%.

[0194] pH changes: 1D: 6.35, 1w: 6.80, 4w: 7.3; 12w: 7.14.

[0195] Cytotoxicity and cell proliferation rate: Grade 0; the proliferation rate of the standard extract was 110% compared with the blank, and 121% after dilution by one time.

[0196] No redness, swelling, oozing, or fluid accumulation occurred at 1 day, 1 week, 4 weeks, and 12 weeks post-surgery.

[0197] Compared to Example 1 containing calcium glycerophosphate, the degradation rate was significantly reduced, cell proliferation was slightly lower, and pH was lower.

Claims

1. A bone repair complex, characterized in that, The raw materials of the bone repair complex include a solid phase and a curing liquid, wherein the solid phase includes glycerophosphate, soluble phytate, and sulfate; the curing liquid is aloe vera mucus; and the structural formula of the soluble phytate is: M is calcium, magnesium, strontium, or zinc; the sulfate is calcium sulfate.

2. The bone repair composite according to claim 1, characterized in that, The ratio of the curing liquid to the solid phase is 0.5~1.5mL:1.0g.

3. The bone repair composite according to claim 1 or 2, characterized in that, The solid phase comprises 30-60 parts by weight of glycerol phosphate, 100-200 parts by weight of soluble phytate, and 40-100 parts by weight of sulfate.

4. The bone repair composite according to claim 1, characterized in that, The soluble phytate is prepared from phytic acid and metal hydroxides or carbonates, wherein the molar ratio of phytic acid to metal hydroxides or carbonates is 1:2 to 5, the pH of the soluble phytate is 6.50 to 7.2, and the metal hydroxides or carbonates are selected from calcium, magnesium, strontium, or zinc hydroxides or carbonates.

5. The bone repair composite according to claim 1, characterized in that, The glycerophosphate is selected from calcium glycerophosphate, magnesium glycerophosphate, or zinc glycerophosphate.

6. The bone repair composite according to claim 1, characterized in that, The aloe vera mucilage is prepared by the following method: the aloe vera is peeled, cut into pieces and crushed, then filtered and sterilized to obtain the aloe vera mucilage. The aloe vera is Aloe barbadensis, Aloe chinensis, Aloe arborescens, Aloe saponaria, Aloe vera var. chinensis, or Aloe vera var. chinensis.

7. A method for preparing a bone repair complex according to any one of claims 1 to 6, characterized in that, The preparation method involves first mixing glycerophosphate, soluble phytate, and sulfate to form a solid phase, then mixing aloe vera mucus and the solid phase at a ratio of 0.5~1.5mL:1.0g to form a mixture; finally, solidifying the mixture yields the bone repair complex.

8. The application of bone repair complexes in the preparation of materials for bone defects, bone injuries, bone trauma, or bone reconstruction, characterized in that, The bone repair complex is the bone repair complex according to claims 1 to 6, or the bone repair complex prepared according to claim 7.

Citation Information

Patent Citations

  • Bone repair material and preparation method and application thereof

    CN111870738A

  • Controllable cured calcium sulfate bone-cementing agent and its preparation method

    CN1876189A